1998
DOI: 10.1023/a:1023238915316
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Heparin-induced thrombocytopenia (HIT) is a common drug induced autoimmune condition. The thrombocytopenia is caused in most cases by an antibody directed against the complex PF4/heparin. Recently, we have induced an experimental model of HIT by idiotypic manipulation. To confirm further the idiotypic involvement of HIT, we have treated successfully three patients with HIT with high-dose intravenous gamma-globulin (IVIG). Our three patients joint other two cases previously reported who were treated with IVIG a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…45,46,[50][51][52][53][54] Similarities to data in Table 2 include median platelet nadir (18 × 10 9 /L) and that most patients were postsurgical (commonly postorthopedic and postcardiac surgery). 45,46,[50][51][52][53][54] Mean age (57 years old) was lower than in the patients in Table 2. 45,46,[50][51][52][53][54] Approximately 46% of patients presented with venous thrombosis at HIT diagnosis, and 15% had major bleeding.…”
Section: Case Reports Using Ivig That Did Not Meet Inclusion Criteriasupporting
confidence: 65%
See 4 more Smart Citations
“…45,46,[50][51][52][53][54] Similarities to data in Table 2 include median platelet nadir (18 × 10 9 /L) and that most patients were postsurgical (commonly postorthopedic and postcardiac surgery). 45,46,[50][51][52][53][54] Mean age (57 years old) was lower than in the patients in Table 2. 45,46,[50][51][52][53][54] Approximately 46% of patients presented with venous thrombosis at HIT diagnosis, and 15% had major bleeding.…”
Section: Case Reports Using Ivig That Did Not Meet Inclusion Criteriasupporting
confidence: 65%
“…46,49,52,53 Betrosian et al 51 and Gul et al 54 reported a positive ELISA but did not report an OD value. Winder et al 50 reported 3 HIT cases with an immunoassay (OD < 2), although each of the patients had an activation assay completed by platelet-rich plasma activation assay. This assay test has become obsolete and the results questioned because of its lower sensitivity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations